2014
DOI: 10.1097/igc.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Staging in Stage I Clear Cell Adenocarcinoma of the Ovary

Abstract: The prognosis for women with stage 1A/IC1 is very good. Surgical staging category was the only independent prognostic factor for RFS in stages IA/IC1 CCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Patients with clear cell carcinoma are typically young and are often diagnosed with stage I–II disease. Therefore, they do not exhibit poor prognosis [ 21 ]. In the present study, the majority of clear cell carcinoma cases presented as stage I or II (46 out of 60 cases) with a 5-year overall survival rate of approximately 80%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with clear cell carcinoma are typically young and are often diagnosed with stage I–II disease. Therefore, they do not exhibit poor prognosis [ 21 ]. In the present study, the majority of clear cell carcinoma cases presented as stage I or II (46 out of 60 cases) with a 5-year overall survival rate of approximately 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Human 3×FLAG-tagged full-length MCM2 ( 3 × FLAG-MCM2-FL ) and 3×FLAG-tagged N-terminal-deficient MCM2 ( 3 × FLAG-MCM2- ΔN) were subcloned using the cDNA from HEK293T cells. PCR primers for MCM2-FL used in this study have been previously described [ 21 ]. The PCR primers for MCM2-ΔN were as follows: forward primer: 5′-AATATGCGGCCGCGCG GGCCACGGAGGACGGCG-3′ and reverse primer: 5′-AGCGGCCGCAAGCAGGCTTGGAGAAACAA-3′.…”
Section: Methodsmentioning
confidence: 99%
“…According to the current retrospective literature, the necessity of systemic lymph node dissection in patients with OCCC is still controversial. Suzuk et al [20] demonstrated that signi cant differences were observed in progression-free survival and overall survival between patients optimally and nonoptimally staged with stages IA/IC1 OCCC, but no signi cant difference was found in those with stages IC2/IC3. Surgical staging category was the only independent prognostic factor for recurrence-free survival in stages IA/IC1 OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is considered that optimal surgical cytoreduction can be defined only if there are no macroscopically visible remains. The aim of cytoreductive surgery is to enhance the effects of cytostatics on possible residual tumor cells [12,13]. When planning the treatment of ovarian cancers, special circumstances and situations must be considered: sparing surgery which preserves woman's fertility, surgery of ovarian cancer with low malignant potential (borderline tumors), surgical treatment of epithelial and germ cell ovarian cancer adjusted to different FIGO stages, use of laparoscopic technique and surgical treatment of ovarian cancer in pregnancy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Only a well trained surgical team can perform all necessary interventions on different abdominal organs, including large and small bowel, liver, spleen, lymph nodes, diaphragm etc. and be a reliable "prognostic factor" in ovarian cancer surgical treatment [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%